ANALISIS PORTOFOLIO BISNIS PT MULTIMEDIA NUSANTARA - , Bobby Boris Baskoro ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Corporate strategy that developed by a diversified company appropriate if the parent company has a high compatibility (fit) with its business units. According to Thompson, Strickland and Gamble (2012) diversification strategy can be justifiable if they are able to create value for shareholders, meaning that the selected business units should have better performance under single corporate umbrella than stand alone independently (stand alone business). Value creation can be done if the company has a value creation insights and special characteristics, so it can build an effective strategic planning process. A multibusiness company usually consists of a parent company and one or more subsidiaries or business units. Multibusiness companies create value by influenced the business units they owned. A good fit between a parent and its business units will create value, a bad one will destroy it. Corporate parenting framework (Campbell & Goold & Alexander, 1995) was developed to address the phenomenon of the many corporate-level companies that have failed in identifying two crucial issues regarding what business units should be included in their portfolio and what approach should be used by companies for upgrading the performance of all their business units. The framework is also developed to complement the concept of core competencies (Hamel & Prahalad, 1990), using structured analysis approach that consists of four steps, namely identifying characteristics of corporate parenting, identifying parenting opportunities and critical success factors of business units and mapping into parenting fit matrix which would describe the position of all business units within the corporate portfolio into five main categories, namely business heartland, heartland edge-of-business, business ballasts, value trap business, and alien business territory, where each position would have different implication strategy to improve its performance in the future. The position of each business unit in the matrix is placed on assessment of the level of concordance between the parent's skills and business need, whereby a high level of concordance between the two will be able to realize the value creation. A qualitative case study was used to understand parenting value creation in Metra Group, there are good fit between the parent and most its business units.